It won't happen to me! Psychosocial factors influencing risk perception for respiratory infectious diseases: A scoping review. Issue 4 (15th April 2021) - Tagini, Sofia; Brugnera, Agostino; Ferrucci, Roberta; Mazzocco, Ketti; Compare, Angelo; Silani, Vincenzo; Pravettoni, Gabriella; Poletti, Barbara
Abstract: Understanding the determinants of risk perception for COVID‐19 might help to promote self‐preventive behaviours. This scoping review aimed to map the extent, variety and characteristics of the evidence on the possible determinants of risk perception for COVID‐like diseases. PubMed, Scopus and Web of Science were searched for original, peer‐reviewed English‐written articles published up to March 2020 and investigating risk perception determinants for respiratory infectious diseases in adults. Titles and abstracts were screened, and full texts were analysed by the first author; when unsure, eligibility was discussed with the last author. Data were collected according to an extraction sheet developed by the first and last authors. The cross‐sectional evidence covers a variety of diseases, countries and timings of testing. Mostly, questionnaires recorded socio‐demographics, media exposure, trust in institutions, disease proximity and knowledge; psychological variables, including personality traits, distress and self‐efficacy, were less investigated. A miscellaneous operationalization of risk perception emerged, including the likelihood of getting sick, perceived dangerousness, concerns or a combination of them. A comprehensive understanding of the substantial amount of evidence may be challenging due to methodological heterogeneity. Referring to uniform theoretical frameworks is recommended; also, longitudinal research may be implemented to probe causal relationships.